Public art as meditation on public time - Tereza Hadravova; Sabrina Muchová (Aisthesis, 2022)
In this paper, we draw attention to temporal aspects of works of art displayed, performed, or held in public spaces, generally designated as public art. We argue that the debate on public art has been biased towards discussing the spatial. We focus on the “temporariness” of public art, the primary temporal feature that has been under scrutiny in recent philosophical literature on public art. We explore arguments it has been woven into. In particular, we discuss and reject using temporariness as the mark dissecting the realm of public art into two different artforms and argue that it is just one of many temporal properties public artworks have and can use to bear meanings. We outline other ways works of public art bear temporal features and interact with temporal properties of spaces they occupy, and argue that those too are, potentially, aesthetically significant. We illustrate some of these with an example of a particular public artistic site, the open-air art gallery «ArtWall» located in Prague, the Czech Republic.